Pengaruh Keaktifan Belajar dan Motivasi Belajar Siswa Terhadap Hasil Belajar Siswa Kelas VII SMP Negeri 2 Sampolawa - Suwarni La Usa; Fatmawati Muhudiri (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The objective of this research was to find out the effect of students’ learning activeness and learning motivation toward students’ learning achievement in the seventh grade of SMPN 2 Sampolawa. The research was an ex-post facto research which using quantitative approach. Population of the research was all students in the seventh grade of SMPN 2 Sampolawa with the total number was 56 students which spread out in two classes. The sample of the research was all population which 56 students. Meanwhile, in the instruments of the researh were questionnaire and documentation. Data was analyzed using multiple linear regression analysis. The result showed that there was effect of students’ learning activeness and learning motivation toward students’ learning achievement in the seventh grade of SMPN 2 Sampolawa. It could be seen from f value was 5.872, and sig. value was 0.005 < 0.05. it meant that H0 was rejected and H1 was accepted. from this result, it could be conluded that there was effect of students’ learning activeness and learning motivation toward students’ learning achievement in the seventh grade of SMPN 2 Sampolawa.